2015
DOI: 10.1186/s12876-014-0226-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of endoscopic steroid injection for prophylaxis of esophageal stenoses after extensive endoscopic submucosal dissection

Abstract: BackgroundEsophageal stenosis following endoscopic submucosal dissection (ESD) is a serious adverse event that makes subsequent management more difficult.MethodsThis parallel, randomized, controlled, open-label study was designed to examine whether local steroid injection is an effective prophylactic treatment for esophageal stenoses following extensive ESD. This single center trial was conducted at the Keiyukai Hospital, a tertiary care center for gastrointestinal disease in Japan [University Hospital Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
200
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(210 citation statements)
references
References 22 publications
8
200
1
1
Order By: Relevance
“…52, 59 Liang et al , utilizing a 6-point Likert scale to measure the frequency and severity of symptoms, found a significant improvement in heartburn scores and regurgitation scores 5 years after RFED therapy. 53 Studies reported a wide range for patients with complete PPI cessation (6.3–86%), though overall PPI use was reduced in 43–89% of patients. 5257 …”
Section: Resultsmentioning
confidence: 99%
“…52, 59 Liang et al , utilizing a 6-point Likert scale to measure the frequency and severity of symptoms, found a significant improvement in heartburn scores and regurgitation scores 5 years after RFED therapy. 53 Studies reported a wide range for patients with complete PPI cessation (6.3–86%), though overall PPI use was reduced in 43–89% of patients. 5257 …”
Section: Resultsmentioning
confidence: 99%
“…Since esophageal stricture sometimes worsens quality of life, various preventive methods have been proposed [4,7,10] . Endoscopic injection of TA is widely used in the prevention of esophageal stricture associated with ESD [8,9] . However, a significant population of patients develop esophageal stricture even after the preventive injection.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic TA injection is one of the most effective treatments for prevention of ESD-associated esophageal stricture [8,9] . However, a significant proportion of patients still develop esophageal stricture requiring EBD even after endoscopic TA injection.…”
Section: Flow Diagrams Of the Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that oral steroid therapy after EBD is an effective strategy for the management of esophageal strictures after complete circumferential ESD. The local injection of triamcinolone acetonide 18) and other systemic steroid therapies 13) are frequently used to prevent esophageal strictures after ESD. Moreover, ESD for esophageal cancer is generally a more difficult technique as compared to ESD for gastric cancer because the working space is small in esophageal ESD.…”
Section: Endoscopic Treatmentmentioning
confidence: 99%